2016
DOI: 10.3949/ccjm.83.s2.06
|View full text |Cite
|
Sign up to set email alerts
|

Fibromuscular dysplasia: Advances in understanding and management

Abstract: Several key findings in recent years have reshaped our understanding of fibromuscular dysplasia (FMD), an uncommon nonatherosclerotic disease of medium-sized arteries that affects mainly women. While the true prevalence of this disease remains unknown, studies suggest that more people may be affected than previously reported. Better understanding of the clinical manifestations and natural history of FMD and advances in diagnostic imaging have altered the clinical approach to managing patients with this uncommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 43 publications
(64 reference statements)
1
41
0
2
Order By: Relevance
“…FMD may represent a nonspecific reaction to a disturbance of the vascular extracellular matrix (18). This inference is supported by the occurrence of FMD in a variety of disorders affecting the extracellular matrix, such as Ehlers-Danlos syndrome, a-1 antitrypsin deficiency, and aortic coarctation (1,(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 96%
“…FMD may represent a nonspecific reaction to a disturbance of the vascular extracellular matrix (18). This inference is supported by the occurrence of FMD in a variety of disorders affecting the extracellular matrix, such as Ehlers-Danlos syndrome, a-1 antitrypsin deficiency, and aortic coarctation (1,(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 96%
“…Fibromuscular Dysplasia. Fibromuscular dysplasia (FMD) is an idiopathic segmental nonatherosclerotic, noninflammatory arteriopathy that predominantly affects women [28,29]. Classification is based on angiographic appearance: either focal or multifocal (string of beads) [30].…”
Section: Medium-vessel Vasculitis Mimicsmentioning
confidence: 99%
“…The most severe complications are acute kidney injury, renal infarction, transient ischemic attack, stroke, myocardial infarction, and mesenteric ischemia. Diagnosis is usually achieved in the presence of clinical manifestations and compatible vascular imaging [28,30,32,33].…”
Section: Medium-vessel Vasculitis Mimicsmentioning
confidence: 99%
“…It is characterized by fibrous tissue formation within the arterial walls leading to arterial narrowing. 1 , 2 Although the prevalence of FMD remains unknown, data from asymptomatic potential kidney donors revealed that 4.4% of them had FMD. 3 , 4 FMD has been associated with various vascular events including aneurysms, artery dissections, and tortousities.…”
Section: Introductionmentioning
confidence: 99%